Competencies of Science Facilitators in Non-formal Learning Contexts - Husin, Wan Nor Fadzilah Wan; Husin, Wan Nor Sariza Wan; Arsad, Nurazidawati Mohamad; Halim, Lilia (Asia Research Network Journal of Education, 2021)
Learning science in non-formal contexts is gaining attention in the effort to enculturate science literacy among the society, thus the science facilitators in institutions/agencies of non-formal learning of Science play a significant role. Therefore the purpose of this research is to identify the competency level of science facilitators and to identify the differences in the level based on gender, academic qualification, and work experience. The research sample comprised 117 science facilitators who are serving in institutions/agencies of non-formal learning of Science. Data analysis based on descriptive statistics used include mean, frequency, standard deviation, and percentage while the inferential statistics used Multivariate Analysis of Variance (MANOVA). The Questionnaire was based on five dimensions, namely dimensions of personal quality, subject knowledge, communication skills, learning evaluation, and learning assistance with 69 items. Results from the descriptive analysis showed that the level of competency of science facilitators is high in all of the dimensions studied. Inferential findings showed that science facilitators’ level of competency is influenced by the factor of academic qualification, where the facilitators with Bachelor’s/Master’s degree academic qualifications have higher competency compared to those with a diploma and Malaysian Certificate of Education (MCE)/ Malaysian High School Certificate (MHSC) academic qualifications. Research findings also showed significant differences in the competency dimensions of personal quality, subject knowledge, and learning evaluation based on academic qualifications. The dimensions of communication skills and learning assistance were the same for facilitators of different academic qualifications. Based on the findings, the selection of facilitators should consider bachelor’s/master’s degree and in the professional development programs should be continuous for facilitators in efforts to empower non-formal Science learning as a complement to formal learning of Science.